Meningkatkan Semangat Komunitas Wanita Tani Melalui Revitalisasi Kebun Bibit Desa Karangmulyo - Alif Khair An Nassaj; Muhammad Luqman Hakim; Hanna Zharifa Marmu’asyifa; Liya Tsanyyatul Khishol; Andre Alfiansyah; Muhammad Afiq (Lembaga Pengembangan Kinerja Dosen, 2024)
The COVID-19 pandemic has had a significant impact on various aspects of life, including the agricultural and environmental sectors in Karangmulyo Village. Community gardens and parks that were once well-maintained are now experiencing a decline in quality and productivity. This village nursery revitalization program aims to overcome the negative impacts of the pandemic, restore land function, and increase the spirit of the women farmer community. Revitalization steps include improving infrastructure, planting adaptive crops, and implementing sustainable agricultural techniques. In addition, this program also emphasizes the importance of community involvement and solidarity through mutual cooperation and discussion activities. It is hoped that this revitalization can improve the welfare of the community as a whole and ensure the sustainability of the village environment